Self-Reliant Framework of India’s Foreign Trade: A Theoretical Perspective. - Malik, Dr M Rashid (The journal of contemporary issues in business and government, 2023)
This paper is theoretical and exploratory in nature. The author tried to develop and propose a framework which suggests the course of action for India to be self-reliant in trade of goods. For India to be self-reliant in foreign trade in goods there are two way strategies- One is to increase the exports of the products by promoting excellence which can have significant impact on the economic performance of the country. Two, simultaneously reducing the import of the products which are critically derailing the resources and robustness of the economy. In this proposed self-reliant framework of India’s foreign trade, which focuses on trade in goods, the author tried to identify three critical areas of export where India should focus by promoting Excellence which will have multiplying effects on the economy. At the same time, three areas of import have been identified which are draining India’s resources, dragging the economic growth and may have cascading effects which can be reduced by promoting self-reliance that is Atmanirbharta.